2020
DOI: 10.1590/0104-530x3339-20
|View full text |Cite
|
Sign up to set email alerts
|

The influence of supplier integration and lean practices adoption on operational performance

Abstract: This study investigates the influence of supplier integration and lean practices on operational performance indicators: cost, quality, delivery, flexibility and speed of new products introduction. The proposed relationships are analyzed using survey data from a sample of 112 medium-sized textile companies in Brazil. The results suggest that supplier integration is significantly and positively associated with the speed of new products introduction, while lean practices are significantly and positively associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…SC integration is considered collaboration and cooperation among all SC departments and members. Previous studies (Janssen et al ., 2020; Lotfi et al ., 2013; Petersen et al ., 2005; dos Santos Bento et al. , 2020) have explained that the SC integration can be enhanced by blockchain unique properties to improve the information-sharing platform among internal and external SC members (Hellani et al ., 2021; Queiroz et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…SC integration is considered collaboration and cooperation among all SC departments and members. Previous studies (Janssen et al ., 2020; Lotfi et al ., 2013; Petersen et al ., 2005; dos Santos Bento et al. , 2020) have explained that the SC integration can be enhanced by blockchain unique properties to improve the information-sharing platform among internal and external SC members (Hellani et al ., 2021; Queiroz et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Supplier integration is positively associated with the speed of new product introduction, but it does not support lean practices for operational performance indicators. Lean practices are positively associated with operational performance indicators, but not with delivery [50].…”
Section: Supplier and Customer Related Lean Practicesmentioning
confidence: 86%
“…Therefore, the implementation of the Lean philosophy in the manufacturing sector is evidenced in an improvement in cost performance, where the elimination of waste increases the optimization of resources and productivity in a high percentage. (Dos Santos et al 2020). Likewise, in another study it was observed that this implementation of Lean helps companies that are in search of continuous improvements, where after applying it, it achieved a reduction of 300 Proceedings of the 4th African International Conference on Industrial Engineering and Operations Management Lusaka, Zambia, April 4-6, 2023 seconds after applying a standardization process and in turn a decrease of 5%.…”
Section: Lean Manufacturingmentioning
confidence: 90%